Pengaruh Cooperative Learning tipe Make a Match terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Tiyasa Tiyasa (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
This study aims to determine the influence of Cooperative Learning Model with Make a Match type on the learning outcomes of fourth grade students in SDN Cibunar 02 Parungpanjang Bogor. The research method was associative quantitative approach with the Posttest Only Control Group Design Method. The sample of the research was 50 students. The research instrument was a test of mathematics learning outcome that consisted of 5 essays. Each of questions had 4 for maximum score and 0 for minimum score. Based on the results of the normality and homogeneity of learning outcomes in the experimental class and the control class, the results of the data in both classes were normally distributed and homogeneous. Furthermore, data analysis techniques used hypothesis test. The results showed the average learning outcome of experimental class were 66.6 while the control class was 54.4. Based on hypothesis test, there were significant differences in the average learning outcomes of the experimental class with the control class. In conclusion, there was the influence of Cooperative Learning Models with Make a Match type on the mathematics learning outcomes of fourth grade students of SDN Cibunar 02 Parungpanjang Bogor.